Сreating a mechanism for broadcasting corporate culture norms and internal PR in order to increase employee engagement - O. S. Suvalov; T. V. Suvalova (Вестник университета)
The aim of the study is to analyse the mechanism for increasing staff engagement through broadcasting corporate values and internal PR. The article substantiates the relevance of informing as a verbal means of positive content. The paper gives an approximate list of proclaimed and denied values. The authors consider corporate events with the aim of conveying the mission, values and ideology of the company to all employees. The study notes the role of regular informing for uniting employees into a single team, forming a sense of pride in the company for the staff. The article reviews the option of monitoring the level of awareness through a feedback questionnaire, notes the need for analysis of incoming data. The paper focuses attention on the formation of personnel identity and loyalty, the use of company symbols, the creation of corporate values and traditions.